Contribution of Local Wisdom as a Halal Tourism Attraction - Abdul Ghofur; Ismanto, Kuat (International Journal of Islamic Business and Economics (IJIBEC), 2022)
The purpose of this paper is to analyze the contribution of local wisdom as a halal tourism attraction. This research is carried out with a qualitative research framework. Primary research data is collected by qualitative research methods, namely through observation, interviews, and documentation. Secondary data is obtained through the assessment of articles, books, research reports, documents, and other sources that are valid and support the theme of the research. Observations are carried out in the region and tourist attractions, while interviews are conducted to the Tourism Office and the managers of tourist attractions, communities, and tourists. The collected data is analyzed descriptively qualitatively. The results of this study show that Pekalongan City has the prospect of becoming a halal tourism destination because it has fulfilled the components of halal tourism (attractions, access, amenities, communication, environment, supporting facilities, and celebration). On the other hand, the attractions and attractions owned by Pekalongan City are interesting and diverse. Pekalongan City has a distinctive and unique local wisdom and can be an object and attraction of regional tourism. In addition, it is also supported by community security and creativity activities that support local wisdom as a tourism attraction. Culture, Islamic traditions, and local wisdom in Pekalongan City have not been maximally packaged into tourist attractions. The implication of this study is that the packaging of local wisdom into a tourist attraction will contribute to the development of regional tourism. The abandonment of local wisdom as a regional tourism attraction will negate Indonesia which is rich in cultural diversity as a differentiator with other countries in the field of halal tourism.